2015
DOI: 10.1111/ppa.12364
|View full text |Cite
|
Sign up to set email alerts
|

The development of tea blister caused by Exobasidium vexans in tea (Camellia sinensis) correlates with the reduced accumulation of some antimicrobial metabolites and the defence signals salicylic and jasmonic acids

Abstract: Blister blight (causal agent, Exobasidium vexans) is an economically devastating disease of tea (Camellia sinensis). To determine what metabolite changes occur with tea blister that could be linked to disease progression, metabolomic approaches were used on E. vexans infected tea from a Darjeeling (India) plantation. Samples were classified according to disease phenotypes, i.e. either healthy or at one of three stages of disease progression. Initial metabolite fingerprinting using Fourier transform infrared (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…This fungus is known to remain dormant during periods of unfavorable conditions, only becoming pathogenic under optimal climatic conditions. If not controlled by fungicides, tea losses due to this pathogen may range from 25 to 43% ( Mur et al., 2015 ). Suitable modeled areas for E. vexans on tea are in Australia, South America, Africa, and Asia.…”
Section: Resultsmentioning
confidence: 99%
“…This fungus is known to remain dormant during periods of unfavorable conditions, only becoming pathogenic under optimal climatic conditions. If not controlled by fungicides, tea losses due to this pathogen may range from 25 to 43% ( Mur et al., 2015 ). Suitable modeled areas for E. vexans on tea are in Australia, South America, Africa, and Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, flavonoids have been found to be elicited by pathogen infections. For example, E. vexans infection elevated the accumulation of quercetin and kaempferol glucosides and kaempferol triglycosides but substantially reduced the accumulation of apigenin and myricetin glycosides [ 76 ]. In summary, flavonoids responded specifically to different insects and pathogens; nevertheless, targeted metabolites and the underlying precise mechanisms of defense against insects and pathogens need in-depth investigations, according to the current studies.…”
Section: Defense Responses Of Flavonoids To Herbivore/pathogen Attack...mentioning
confidence: 99%
“…Furthermore, E. vexans infection induced the accumulation of C, EC, EGC, and EGCG. These results suggested that herbivory and pathogen attacks elicited the differences in catechin metabolism [ 76 ]. Among seven catechins, both C and EGCG were effectively triggered upon attack by E. grisescens , E. obliqua , E. onukii , C. fructicola , and E. vexans , which suggested that C and EGCG could respond conservatively to different herbivores and pathogens, while other components responded differently.…”
Section: Defense Responses Of Flavonoids To Herbivore/pathogen Attack...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to habitat suitability modelling studies, it has a suitability of 10.20% ( C. sinensis ) and 11.90% ( C. assamica ), and areas with increased future risk include southeast Asian countries (Tibpromma et al, 2021). Research suggests that owing to E. vexans infection, the content of important defence hormones, salicylic acid and jasmonic acid in tea plants is downgraded, thus, disturbing the defence signalling and many potentially antimicrobial compounds to aid disease progression (Mur et al, 2015). Colletotrichum acutatum is yet another significant tea anthracnose pathogen.…”
Section: Fungal Diseases and Pest Infestation In Teamentioning
confidence: 99%